Mobile marketing in the 21st century: a partial least squares structural equation modelling approach - Pan, Vic-Qi; Chew, Pai-Qin; Cheah, Amy Shun-Gui; Wong, Choy-Har; Tan Han, Garry Wei (2015)
Mobile marketing (m-marketing) adoption has not been a preferred selection among consumers although the benefits are tremendous. As the cost of implementing the system can be expensive the study explores on the factors that influence the decision of consumers to adopt m-marketing. Using technology acceptance model (TAM), the framework was extended with social influence (SI), personal innovativeness in information technology (PIIT) and perceived enjoyment (PE). The data was collected from 108 users using self-administered questionnaire and subsequently tested using SmartPLS. Only PIIT is a non-significant construct based on the investigation. The findings bring significant benefits to marketers who wish to integrate m-marketing in their advertising budget. In addition, the study provides unprecedented methods in reaching to mobile consumers.